Bridging N-aminoisocyanate ligands in heterobimetallic complexes: coupling of zirconium hydrazinediides and transition-metal carbonyls - Gehrmann, Thorsten; Lloret Fillol, Julio; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2010)
Reaction of the zirconium complex [Zr(N2TBSNpy)(═NNPh2)(py)] with metal carbonyl complexes yielded the heteronuclear complexes [(N2TBSNpy)(py)Zr{μ-OCNNPh2-1κC:2κ2NO}Mm(CO)n] (M = Cr, Mo, W (m = 1, n = 5), Fe (m = 1, n = 4), Mn (m = 2, n = 9)). The bridging N-aminoisocyanato ligands in the dinuclear complexes were formed by [2 + 2] cycloaddition of the Zr═NNR2 unit and coordinated CO.